Kajian UMKM Naik Kelas di Kabupaten Sleman Tahun 2020 - Suryanto, Rudy; Junaidi, Junaidi (Jurnal Akuntansi, Keuangan, dan Manajemen, 2022)
Purpose: This study reveals the condition of MSMEs in the Sleman Regency area and how efforts must be made so that MSMEs are promoted. Research methodology: Qualitative approach with interviews and focus group discussions. Results: Based on the studies conducted, it is shown that the journey of MSMEs to advance to class is not an easy thing. At the pilot stage, SMEs must pass through what is called the "valley of death". The next stage of development is a period of growing; and advancement, where each stage of each MSME is different. For MSMEs to move up a class, a strategy is needed with a focus on efforts to increase sales turnover. Limitations: Although the instrument has been designed to be generally accepted, due to time constraints and data availability, it is possible that there may still be sectoral bias, especially for sectors outside trade, services, and manufacturing. Contribution: This study is expected to help contribute to the stages of development of MSMEs in Sleman Regency, so that it can help the Sleman Regency government to formulate policies related to MSMEs advancing to class.